The Influence factors of local leaders' roles toward the community development decision-making in Bamyan, Afghanistan - Man, Norsida; Faizi, Mohammad Salem; Mohd Nawi, Nolila; Ahmadzai, Mohammad Khal (I J S T R Research Publications, 2021)
The study identified the influencing factors on the roles of the local leaders in decision-making for community development in Bamyan Province, Afghanistan. In an effort to rebuild the nation recovering from decades long of war, the efficiency of governance in development is crucial to deliver the success. Yet, the main problem that poses a challenge to achieve the goal is the indefinite information about the community development and the roles of the local leaders. A self-administered questionnaire was designed and subsequently distributed to 384 community members. Factor and regression analysis were performed to identify the influencing factors. The result shows that three factors have the most impact on community development decision-making. The result obtained from the study shows that Bridging Standardized Beta value is 31.5, Guiding Standardized Beta value is 22.8 and Accountability Standardized Beta value is 11.5 these three factors are significant (P-value 0.000<0.05). Therefore, relationship, cooperation, sponsor and trust are the important issues in a community development decision making for the consideration of local leaders as his role.